A new species of Physoschistura (Pisces: Nemacheilidae) from northern Thailand - Suvarnaraksha, Apinun (Zootaxa, 2013)
Physoschistura chulabhornae, new species, is described from Maechaem River, a tributary of Ping River, upper Chaophraya River drainage, Chiangmai province, Thailand. It is distinguished from all other known species of Physoschistura in having an incomplete lateral line reaching at least to the origin of the anal fin with 62–83 lateral-line canal pores, the dorsal-fin origin slightly in front of the pelvic-fin origin, no axillary pelvic lobe, and a suborbital flap in the shape of a hammer head in the male.